Neuropsychological Performance in First-Episode Adolescents with Schizophrenia: A Comparison with First-Episode Adults and Adolescent Control Subjects - White, Tonya; Ho, Beng-Choon; Ward, Julianna; O’Leary, Daniel; Andreasen, Nancy C. (Biological psychiatry (1969), 2006)
The goal of this study was to compare the extent of cognitive deficits between adolescents and adults early in the course of schizophrenia. A comprehensive neuropsychological battery was performed on 49 adolescents with childhood- or adolescent-onset schizophrenia, 139 adults with adult-onset schizophrenia, 32 healthy adolescent volunteers, and 240 healthy adult volunteers. Both patient groups were assessed early in the course of their illness and were matched to their respective control groups on age and parental education. The adolescent patients performed significantly worse than the adult patients on tasks of working memory, language, and motor function. The healthy adolescents also performed significantly worse than the healthy adults in working memory and language tasks but were significantly better than the adults in motor function. When accounting for developmental differences in the control group, only motor performance was worse in the adolescent patients compared with the adult patients. These findings, when coupled with published retrospective studies reporting greater cognitive deficits in earlier onset schizophrenia, implicate a cessation in development in specific cognitive domains following the onset of schizophrenia in adolescent patients.